Predicting the impacts of chemical pollutants on animal groups. (September 2022) - Michelangeli, Marcus; Martin, Jake M.; Pinter-Wollman, Noa; Ioannou, Christos C.; McCallum, Erin S.; Bertram, Michael G.; Brodin, Tomas
Abstract : Chemical pollution is among the fastest-growing agents of global change. Synthetic chemicals with diverse modes-of-action are being detected in the tissues of wildlife and pervade entire food webs. Although such pollutants can elicit a range of sublethal effects on individual organisms, research on how chemical pollutants affect animal groups is severely lacking. Here we synthesise research from two related, but largely segregated fields – ecotoxicology and behavioural ecology – to examine pathways by which chemical contaminants could disrupt processes that govern the emergence, self-organisation, and collective function of animal groups. Our review provides a roadmap for prioritising the study of chemical pollutants within the context of sociality and highlights important methodological advancements for future research. Highlights: Wildlife are exposed to an increasing number and diversity of chemical pollutants. Chemical pollutants can elicit a range of sublethal effects on individual organisms, but research on how these contaminants affect social interactions and animal groups is severely lacking. It is imperative that perspectives from behavioural ecology and ecotoxicology are integrated, to increase our understanding of how contaminant effects on individuals might cascade to group-level processes. We present a conceptual framework for researchers and practitioners to guide the study of how chemical pollutants might affect the emergence, organisation, and function of animal social groups.